Indonesian foreign policy and its response to South China Sea affairs for regional stability - Albert Agung Wijaya; Priyanto Priyanto; Muhammad Hadianto (Strategi Perang Semesta, 2022)
This research explains the relationship between Indonesian foreign policy and taking the case studies of conflicts in the South China Sea. Today the dispute between the two major countries, such as America and China, is increasingly heating up in the South China Sea discourse, coupled with the increasing dynamics of the strategic environment that directly impact Indonesia's foreign policy and politics. The research method used in this research is a qualitative research method, supported by literature studies. In international politics, Indonesia has determined its position as a country that adheres to the principle of active free foreign policy, which in terms of foreign policy, Indonesia will not be influenced by the hands of other countries. This paper shows that Indonesia's defense policies and strategies in anticipation of the South China Sea conflict have not been properly announced. It was found that defense policy and strategy have not been in line with the foreign policy that pays special attention to the dynamics of the Southeast Asian region, including in the South China Sea. In addition, the latest defense policies and strategies have not paid attention to the dynamics of the South China Sea conflict. Indonesia's defense policy and strategy still consider that the conflation in the South China Sea can be resolved through soft power and does not anticipate the use of hard power that will have implications for Indonesia's national interests.